The Sneeuberg: A new centre of floristic endemism on the Great Escarpment, South Africa - Clark, V.; Barker, N.; Mucina, Ladislav (Elsevier, 2009)
The Sneeuberg mountain complex (Eastern Cape) comprises one of the most prominent sections of the Great Escarpment in southern Africa but until now has remained one of the botanically least known regions. The Sneeuberg is a discrete orographical entity, being delimited in the east by the Great Fish River valley, in the west by the Nelspoort Interval, to the south by the Plains of Camdeboo, and to the north by the Great Karoo pediplain. The highest peaks range from 2278 to 2504 m above sea level, and the summit plateaux range from 1800 to 2100 m. Following extensive literature review and a detailed collecting programme, the Sneeuberg is reported here as having a total flora of 1195 species of which 107 (9%) are alien species, 33 (2.8%) are endemic, and 13 (1.1%) near-endemic. Five species previously reported as Drakensberg Alpine Centre (DAC) endemics are now known to occur in the Sneeuberg (representing range extensions of some 300–500 km). One-hundred-and-five species (8.8%) are DAC near-endemics, with the Sneeuberg being the western limit for most of these. Ten species (0.8%) represent disjunctions across the Karoo Interval from the Cape Floristic Region (CFR) to the Sneeuberg. In all, some 23 significant range extensions, eight new species, and several rediscoveries are recorded. We conclude by recognising the Sneeuberg as a new centre of endemism along the Great Escarpment, with floristic affinities with the Albany Centre and the DAC, and links to the CFR.